Comparing prognostic value of lung ultrasound scores in predicting outcome of shock patients: an observational study - Negi, Poonam; Giriraj, Manjunath (International Journal of Research in Medical Sciences, 2025)
Background: Shock is a common causes of mortality in ICU. Several scoring systems have been developed to grade the severity of illness. These systems are moderately accurate in predicting survival. Several scoring systems like APACHE, SOFA,SAPS, MODS etc have been used to risk stratify patients in ICU. The lung ultrasound score (LUSS) has been regarded as semi quantitative score to measure lung aeration loss. LUSS can be compared to scoring systems like acute physiology and chronic health evaluation II (APACHE II) and sequential organ failure assessment (SOFA). Methods: Our study was a prospective observational study. 100 patients who fulfilled the inclusion criteria for shock were included. Their APACHE II scores at admission and 24 hours were calculated. Similarly, SOFA scores at 24 and 48 hours post admission were calculated. Lung ultrasound examination was done at four regions of chest and scores noted. All the three scores were statistically analyzed for length of hospital stay, ICU stay, ventilator days and the outcome. Results: Out of 100 cases satisfying the inclusion and exclusion, it was observed that high lung ultrasound scores were associated with increased mortality and number of days on mechanical ventilator. This association was statistically significant. Findings also correlated with high APACHE II and SOFA scores. All the above findings were statistically significant. Conclusions: High lung ultrasound scores at admission were directly related with mortality and increased number of days on mechanical ventilator.